2007
DOI: 10.1007/s10822-007-9112-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of biaryl piperidine and 4-amino-2-biarylurea MCH1 receptor antagonists using QSAR modeling, classification techniques and virtual screening

Abstract: This paper presents the results of an optimization study on biaryl piperidine and 4-amino-2-biarylurea MCH1 receptor antagonists, which was accomplished by using quantitative-structure activity relationships (QSARs), classification and virtual screening techniques. First, a linear QSAR model was developed using Multiple Linear Regression (MLR) Analysis, while the Elimination Selection-Stepwise Regression (ES-SWR) method was adopted for selecting the most suitable input variables. The predictive activity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 32 publications
0
28
0
2
Order By: Relevance
“…Mesmo que a não interpretação de um modelo não impeça sua utilização para fins de predição, caso seja possível interpretá-lo, reforça a utilidade da equação obtida para explicar o problema em estudo. 23,[41][42][43][44] Outro fato importante a ser considerado neste estudo é que o mecanismo de ação dos compostos estudados contra o P. falciparum 3D7 não é conhecido. Assim, a interpretação mecanística pode ser baseada apenas nos descritores moleculares selecionados, seus significados gerais e por comparação com os resultados de outros estudos QSAR.…”
Section: Figura 4 Resultados Dos Estudos De Validação Cruzada Lno (Aunclassified
“…Mesmo que a não interpretação de um modelo não impeça sua utilização para fins de predição, caso seja possível interpretá-lo, reforça a utilidade da equação obtida para explicar o problema em estudo. 23,[41][42][43][44] Outro fato importante a ser considerado neste estudo é que o mecanismo de ação dos compostos estudados contra o P. falciparum 3D7 não é conhecido. Assim, a interpretação mecanística pode ser baseada apenas nos descritores moleculares selecionados, seus significados gerais e por comparação com os resultados de outros estudos QSAR.…”
Section: Figura 4 Resultados Dos Estudos De Validação Cruzada Lno (Aunclassified
“…In other words, the in silico procedure minimizes the time and cost associated with identifying new leads. Virtual screening was performed by insertion, deletion and substitution of different substituents on the original molecules and the effects of structural modifications on the biological activity were investigated (19). Then, the domain of QSAR model application was defined for using the model for screening new compounds.…”
Section: In Silico Screeningmentioning
confidence: 99%
“…To estimate the predictive power of a QSPR model, the following parameters were used [20]: (i) square correlation coefficient R 2 between the predicted and observed property; (ii) coefficients of determination (predicted vs. observed property R 2 0 , and observed vs. predicted property R' 2 0 ); (iii) slopes k and k' of regression lines (predicted vs. observed property, and observed vs. predicted property, with the intercept set to 0) through the origin. In addition, we calculated the r 2 m value for external validation of the RBFNNs model according to Roy and Roy [21].…”
Section: Predictive Power Of Qspr Model (Validation Of External Predimentioning
confidence: 99%
“…A value of r 2 m > 0.5 may be taken as an indicator of good external predictability. We concluded that a QSPR model had an acceptable predictive capability if the following conditions were satisfied [20]: …”
Section: Predictive Power Of Qspr Model (Validation Of External Predimentioning
confidence: 99%